Improving Sexual and Gender Minority Cancer Care: Patient and Caregiver Perspectives From a Multi-Methods Pilot Study - Kano, Miria; Jaffe, Shoshana Adler; Rieder, Stephanie; Kosich, Mikaela; Guest, Dolores D.; Burgess, Ellen; Hurwitz, Ariel; Pankratz, Vernon Shane; Rutledge, Teresa L.; Dayao, Zoneddy; Myaskovsky, Larissa (Frontiers in Oncology, 2022)
Purpose: Up to 1 million sexual and gender minority (SGM) individuals in the United States have histories of cancer. Our paper presents findings from a pilot study to identify gaps and opportunities to improve cancer care for SGM patients and caregivers at the University of New Mexico Comprehensive Cancer Center. Methods: Between June, 2020 and July, 2021, we used a multi-methods research design to collect qualitative and quantitative data regarding cancer patient and caregiver quality of life (QoL) and experiences of cancer and survivorship care. We used PROMIS validated measures to determine patient and caregiver QoL. Results: We recruited 10 SGM cancer patients and 8 heterosexual, cisgender (H/C) patient comparators, and their self-identified informal cancer caregivers (n=36, dyad total n=18). Summaries of PROMIS measures within the four groups of participants suggest that heterosexual, cisgender (H/C) patients reported higher fatigue and stronger pain intensity than SGM patients while SGM patients reported greater anxiety than H/C. H/C patients also reported more emotional support and companionship, whereas SGM patients reported higher levels of social isolation, which is congruent with qualitative findings In qualitative interviews, SGM patients and caregivers articulated experiences of anti-SGM stigma and discrimination contributing to minority stress that influenced cancer care. SGM dyads had more trepidation and/or medical mistrust than H/C individuals when meeting staff and oncologists and were less comfortable questioning cancer care. SGM patients discussed desires to have more direct conversations with their oncologists about their sexual orientation and gender identities (SOGI) and sexual health. All caregivers experienced a lack of support and information pertaining to their loved one’s treatment, side effects and best way to provide care. Conclusions: This study demonstrates that prior stigmatizing experiences contribute to minority stress and medical mistrust for SGM cancer patients and their caregivers, and speaks to the importance of decentering normative assumptions regarding patient and caregiver SOGI, roles and needs, and degrees of social support and isolation, at an individual as well as societal level. Cancer centers need to do more to acknowledge SGM patient preferences in order to optimize care for underserved SGM cancer patients and their caregivers.